2010
DOI: 10.1074/mcp.m000153-mcp201
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Phosphoproteomic Changes Induced by Nucleophosmin-Anaplastic Lymphoma Kinase (ALK) Highlight Deregulation of Tumor Necrosis Factor (TNF)/Fas/TNF-related Apoptosis-induced Ligand Signaling Pathway in ALK-positive Anaplastic Large Cell Lymphoma

Abstract: The oncogenic fusion protein nucleophosmin-anaplastic lymphoma kinase (NPM-ALK), found exclusively in a subset of ALK-positive anaplastic large cell lymphoma, promotes tumorigenesis by exerting its constitutively active tyrosine kinase activity. Thus, characterization of the NPM-ALK-induced changes in the phosphoproteome will likely provide insights into the biology of this oncoprotein. To achieve this goal, we used a strategy of combining sequential affinity purification of phosphopeptides and LC/MS. GP293 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Thus, phosphorylation of HuR by the serine-threonine kinases cdk1, PKCd, or pKCa has been reported to induce HuR translocation into the cytoplasm and modulate its RNA-binding properties (26). Since HuR is present in the cytoplasm of ALCL-derived cells, such modifications could take place in ALCLs where different serine-threonine kinases are at work (29,30), but again, they would not rely specifically on the expression of NPM-ALK. The specificity brought about by the oncogenic tyrosine kinase NPM-ALK is reflected by enhanced binding of HuR to its target mRNAs and increased engagement of HuR into actively translating polysomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, phosphorylation of HuR by the serine-threonine kinases cdk1, PKCd, or pKCa has been reported to induce HuR translocation into the cytoplasm and modulate its RNA-binding properties (26). Since HuR is present in the cytoplasm of ALCL-derived cells, such modifications could take place in ALCLs where different serine-threonine kinases are at work (29,30), but again, they would not rely specifically on the expression of NPM-ALK. The specificity brought about by the oncogenic tyrosine kinase NPM-ALK is reflected by enhanced binding of HuR to its target mRNAs and increased engagement of HuR into actively translating polysomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found evidence of tyrosine phosphorylation of multiple proteins in the tumor necrosis factor (TNF) signaling pathway. Using western blotting, we validated that the induction of the tyrosine phosphorylation of several TNF pathway signaling molecules by NPM-ALK, including RIP, TRAP1 and FAF1 [Wu et al 2010]. In support of their functional importance in this type of lymphoma, we knocked down the expression of TRAP1 using siRNA, and found that this treatment significantly sensitized ALK+ALCL cell lines to TRAIL-and doxorubicin-induced apoptosis.…”
Section: Mass Spectrometry Studies: Identifying Novel Pathways That Mmentioning
confidence: 99%
“…Specifically, 506 phosphoproteins (617 phosphopeptides and 767 phosphorylation sites) were identified. Our method was designed to purify all phosphopeptides, and thus, we were able to detect a large number of serine/threonine phosphorylated proteins [Wu et al 2010].…”
Section: Mass Spectrometry Studies: Identifying Novel Pathways That Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Another phosphoproteomic analysis of cells with NPM-ALK expression identified targets in TNF family-related apoptotic and metabolic pathways. 66 Proteomic analysis of Jurkat cells expressing NPM-ALK identified increased expression of proteins involved in signaling pathways downstream of NPM-ALK, including STAT3. 67 A different proteomic screen identified 254 NPM-ALK binding partners involved in wide-ranging biological processes, including metabolic pathways.…”
mentioning
confidence: 99%